Analisis Penerapan Harga Pokok Produksi pada UMKM Rumah Parquet Bogor - Eika Najla Az-Zahra; Meutya Febriyani; Gaitsa Zahira Shofa; Meylani Dwi Lestari; Yuni Tri Astuti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In recent years, demand for these products has increased along with awareness of the beauty and durability of bengkirai wood. Although SMEs contribute significantly to the Indonesian economy, they face challenges, including access to financing and production efficiency. This study aims to understand how Rumah Parquet accounts for costs related to maintaining environmental quality in its production process. The methodology used included interviews and regression data analysis to calculate Cost of Goods Manufactured (COGS), Operating Expenses (BOP), and profit and loss statements. The results show that Rumah Parquet has not fully integrated environmental quality costs in the COGS calculation, which has an impact on profitability and business sustainability. The findings provide insights for industry players on the importance of better cost management to improve product competitiveness. This research also contributes to the literature by highlighting environmental aspects in cost calculation in the SME sector.